RELATIONSHIP BETWEEN PERIAPICAL LESIONS AND MAXILLARY SINUS EVALUATED BY USING SMALL FOV OF CBCT IN HOMEOSTASIS CONTEXT OF INTRAORAL REHABILITATION: A CASE RAPORT - Cristina Antohi; Liana Aminov; Danisia Haba; Yllka Decolli; Laura Elisabeta Checherita; Radu Eduard Cernei (Romanian Dental Association for Education, 2020)
Periapical lesions are a common cause of odontogenic sinusitis. The purpose of our article was to demonstrate the importance of performing a CBCT even with a small FOV in complex cases of endodontics. We reported the case of a 40-year-old woman where we improved a CBCT examination with a small FOV . That was useful for making a differential diagnosis between a odontogenic sinusitis given by the presence of an existing periapical lesion in relation to it and an existence of a sinus pathology independent of this lesion like mucosal antral cyst (MAC) or mucous retention cyst (MRC).